Picture Story Media to Improve Reading Ability in 2nd grade students at SD Gajah Mada - Simanjuntak, Vitalia Hanako Murni; Fernando De Napoli Marpaung; Muhammad Fadli; Supriadi (CV. Mitkom Indotama, 2024)
This study examines the effectiveness of picture story media in enhancing the reading abilities of second-grade students at SD Gajah Mada. Reading is a crucial skill for elementary students, but many face challenges in developing this skill, as evidenced by the average reading score of 63 at the school. To address this issue, picture story media was introduced as an engaging and interactive learning tool aimed at improving students' reading comprehension and motivation. Classroom action research (CAR) was employed, involving a reflective cycle of planning, action, observation, and reflection. In Cycle 1, the average reading score of students increased from 50.3% to 63.7% after implementing picture story media, with 65.8% of students meeting the passing criteria. Cycle 2 showed further improvement, with the percentage of students scoring between 75-100 rising from 43% to 93.2% by the end of the cycle. These results highlight the significant impact of picture story media in boosting students' reading skills and engagement. The findings support the use of visual aids in education, demonstrating that picture story media can effectively enhance reading abilities among young learners. The study contributes to the field of language education and provides practical insights for teachers in selecting effective learning media. Future research is suggested to explore the long-term effects of picture story media and its application in various educational contexts.